Consensus subtypes of hepatocellular carcinoma associated with clinical outcomes and genomic phenotypes. Issue 6 (29th June 2022) - Lee, Sung Hwan; Yim, Sun Young; Jeong, Yun Seong; Li, Qi‐Xiang; Kang, Sang‐Hee; Sohn, Bo Hwa; Kumar, Shwetha V.; Shin, Ji‐Hyun; Choi, You Rhee; Shim, Jae‐Jun; Kim, Hayeon; Kim, Ji Hoon; et al.
Abstract: Background and Aims: Although many studies revealed transcriptomic subtypes of HCC, concordance of the subtypes are not fully examined. We aim to examine a consensus of transcriptomic subtypes and correlate them with clinical outcomes. Approach and Results: By integrating 16 previously established genomic signatures for HCC subtypes, we identified five clinically and molecularly distinct consensus subtypes. STM (STeM) is characterized by high stem cell features, vascular invasion, and poor prognosis. CIN (Chromosomal INstability) has moderate stem cell features, but high genomic instability and low immune activity. IMH (IMmune High) is characterized by high immune activity. BCM (Beta‐Catenin with high Male predominance) is characterized by prominent β‐catenin activation, low miRNA expression, hypomethylation, and high sensitivity to sorafenib. DLP (Differentiated and Low Proliferation) is differentiated with high hepatocyte nuclear factor 4A activity. We also developed and validated a robust predictor of consensus subtype with 100 genes and demonstrated that five subtypes were well conserved in patient‐derived xenograft models and cell lines. By analyzing serum proteomic data from the same patients, we further identified potential serum biomarkers that can stratify patients into subtypes. Conclusions: Five HCC subtypes are correlated with genomic phenotypes and clinical outcomes and highly conserved in preclinical models, providing a framework for selecting the most appropriate models for preclinical studies. Abstract : image